Um estudo para escolha do SGBD em processos de reengenharia orientada a objetos - Morais, Rinaldo Macedo de (Universidade Federal de São Carlos, 2003)
A process for the database management system (DBMS) choice in the forward engineering stage, in an object-oriented reengineering is presented. The process was instanced for two particular DBMSs Jasmine and Caché, which a forward engineering case study was developed. The legacy system taken as example was submitted to the reengineering process being used the Sybase relational database management system. This same system was used following the process described in this work and having the Jasmine and Caché DBMSs to data persistence. Of this way, three versions could be obtained for a same system. A comparative analysis of three versions also consists of this work.
Keywords: Engenharia de software; Reengenharia orientada a objetos; Banco de dados orientado a objetos; Banco de dados objeto-relacional; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO